Biological Effects of Anti-RANKL Antibody and Zoledronic Acid on Growth and Tooth Eruption in Growing Mice - Motoki Isawa (Nature Portfolio, 2019)
Abstract The anti-bone resorptive drugs denosumab, an anti-human-RANKL antibody, and zoledronic acid (ZOL), a nitrogen-containing bisphosphonate, have recently been applied for treatment of pediatric patients with bone diseases, though details regarding their effects in growing children have yet to be fully elucidated. In the present study, we administered these anti-resorptive drugs to mice from the age of 1 week and continued once-weekly injections for a total of 7 times. Mice that received the anti-RANKL antibody displayed normal growth and tooth eruption, though osteopetrotic bone volume gain in long and alveolar bones was noted, while there were nearly no osteoclasts and a normal of number osteoblasts observed. In contrast, ZOL significantly delayed body growth, tooth root formation, and tooth eruption, with increased osteoclast and decreased osteoblast numbers. These findings suggest regulation of tooth eruption via osteoblast differentiation by some types of anti-resorptive drugs.